The Demand for Capital Goods by Manufacturers: A Study of Quarterly Time Series - de Leeuw, Frank (Econometrica, 1962)
Quarterly time series for all manufacturing are used in this study to test the relationship between plant and equipment expenditures and (a) output and capacity, (b) the flow of internal funds, and (C) the level of corporate bond yields. The study makes use of a newly derived capacity index for all manufacturing and experiments with a number of different lag distributions. THE PURPOSE of this paper is a simple one: to confront some widely held hypotheses about the demand for capital goods with some widely used quarterly figures measuring business investment. The hypotheses relate to the influence on investment of output and capacity, of gross profits less dividends, and of rates of interest. The figures are the Commerce-SEC quarterly series on capital expenditures by manufacturers, and other manufacturing statistics. The figures and the hypotheses are so often used together in analyzing current business developments that it seems profitable to attempt to relate them systematically.2 In doing so, furthermore, byproducts of interest will be developed, namely, an index of manufacturing capacity and some experimentation with lag distributions. The first section of the paper will present the hypothesis to be tested and reduce it to a form which relates to available quarterly time series. The second section will develop and modify the quarterly time series for manufacturing so that they relate as closely as possible to the final hypothesis of Section 1. The third section will present the results of testing the hypothesis. The principal substantive indication of the paper will be that under certain assumption as to lags, a modified acceleration principle variable (capital